Pengaruh Influencer terhadap Minat Beli - Muhammad Sandi Prasetio; Dio Bagas Alkausar; Adiati Hardjanti (Journal on Education, 2023)
This study aims to examine and analyze the effect of perceived credibility, trust, perceived behavioral control, subjective norms, on attitude toward the influencer dan purchase intention in branf Thanksinsomnia. The sample used in this study are 181 respondents. The sampling technique used was purposive sampling. The data were analyzed using the Structural Equation Model (SEM) method. The results of this study indicate that perceived credibility has a positive effect on attitude toward the influencer, trust has a positive effect on attitude toward the influencer, perceived behavioral control has a positive effect on attitude toward the influencer, subjective norms has a positive effect on attitude toward the influencer and attitude toward the influencer has a positive effect on purchase intention.